PENGARUH PEMBERIAN MINUMAN ISOTONIS DAN PISANG TERHADAP KADAR GLUKOSA DARAH ATLET TENIS LAPANGAN UNIVERSITAS NEGERI PADANG - YOGI ANDRIA (Jurnal Sporta Saintika, 2019)
The problem in this study is that many athletes do not pay attention to nutrition and drinks consumed while playing tennis. It is feared that it can affect performance when competing, so it is necessary to do research on the nutrition and drinks consumed by field tennis athletes at Padang State University. This study aims to determine the effect of giving isotonic drinks and bananas on blood glucose levels in tennis tennis athletes. The research method used was an experiment with the same subject design (treatment by subjects designs). The population in this study were tennis athletes in Padang State University totaling 35 people. The research sample of 20 male tennis athletes taken by purposive sampling technique. The instrument for measuring blood glucose levels uses the Glucometer. The data analysis technique used is ANOVA (one way) at a significant level α = 0.05. The results show that isotonic and banana drinks during playing tennis have not been able to maintain blood glucose levels, as evidenced by differences in blood glucose levels before and after playing tennis. Isotonic drinks are better at maintaining blood glucose levels after playing tennis compared to bananas with a significant difference (p <0.05).